SPORT CLUBS, EVENTS AND TOURISM: THE CASE OF SPORT EVENTS IN NITERÓI USING STAKEHOLDERS’ VIEWS - Tadini, Rodrigo; Gauna Ruíz de León, Carlos; Gandara, José Manoel (Revista Hospitalidade, 2019)
This present study aims to understand the relationship between clubs and sporting events in the municipality of Niterói, Rio de Janeiro, Brazil, using the perspective of sports tourism. This town, located on the eastern bank of the Guanabara Bay, in front of the famous and now Olympic city of Rio de Janeiro, is a city with a high tourism potential and a solid sports tradition, accommodating the first three Olympic clubs in Brazil founded in the 1880. In terms of the development of this study, an exploratory qualitative-quantitative analysis was planned to observe the impact of Olympic clubs and their successors at Niterói sporting events. For this purpose, between February and April of 2018, 7 interviews were conducted with different stakeholders of the sporting events in order to collect official data and detect the culture of sporting events in the city nowdays. The results of the study showed the main sports modalities and areas of sporting events in the city. In addition, this research pointed out that after years of development of their sports clubs, changes in the Niteroi’s society affected the participation of people in traditional sports practices within the club environment. These changes directly influenced the consumption of sports activities and automatically the routine of sports clubs and sporting events in the city.